Graphisme et praxis chez Ernest Cormier, « architecte et ingénieur-constructeur » : le « pavillon principal » de l’Université de Montréal - Gournay, Isabelle (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 1989)
This article examines drawings for the “main pavilion” of the Université de Montréal built on Mount Royal between 1928 and 1943. A collection of these drawings will be exhibited at the cca in the spring of 1990. Cormier’s cosmopolitan background as both an architect and an engineer is mentioned briefly, as is the evolution of the project from a traditional academic ensemble of separate pavilions to the present “megastructure.” This dramatic change is demonstrated by the modernization of drawing techniques taught at the Ecole des Beaux-Arts in Paris and the replacement of large renderings in watercolours by photographs of the preparatory model as a promotional medium. All of Cormier’s drawings reflect his French-inspired approach to design and stress the logical expression of both structure and ornamentation. The 1,300 working drawings for the final project form an exceptionally homogeneous ensemble that reveals the architect’s tight control over his small team of highly qualified draughtsmen and his personal involvement at every stage of the design process.